Analysis of the impact of the community development program of PT Pertamina Patra Niaga integrated Terminal Pangkalbalam on local community empowerment - Ramadhani, Tiara; Ningsih, Rani Ade; Muti'ah, Afifah Khairul; Sandhika, Devraldo (Privietlab, 2025)
This study discusses the implementation of the PELIKAS Program (Utilization of Organic Waste for Social Independence) as a form of Corporate Social Responsibility (CSR) for PT Pertamina Patra Niaga Integrated Terminal Pangkalbalam in Bukit Besar Village, Pangkalpinang City. The background of this program is the increasing volume of household organic waste, the limited capacity of the Final Disposal Site (TPA), and the high unemployment rate of the community. Through a community development approach, this program integrates organic waste management with community economic empowerment, especially farmer women groups (KWT), through the cultivation of Black Soldier Flies (BSF) or maggot larvae. The research uses a descriptive qualitative method with interview, observation, and documentation techniques. The results of the study show that the PELIKAS program has a positive impact on three main aspects: (1) the environment, by reducing the volume of organic waste and increasing soil fertility with kasgot; (2) social, through increasing community participation and solidarity, as well as the distribution of crops to vulnerable groups; and (3) the economy, by increasing the income of KWT members and developing products with selling value such as organic fertilizers and processed foods. However, challenges remain in terms of institutional and financial sustainability. The conclusion of this study confirms that PELIKAS is a CSR model based on community empowerment that is effective and can be replicated in other regions to support the achievement of Sustainable Development Goals (SDGs) related to the environment, food security, and economic equality.